2018
DOI: 10.1634/theoncologist.2018-0077
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Therapy in Premenopausal Hormone Receptor Positive/Human Epidermal Growth Receptor 2 Negative Metastatic Breast Cancer: Between Guidelines and Literature

Abstract: This review provides clinicians with an overview on the available data regarding endocrine treatment of hormone receptor positive (HR+) metastatic breast cancer (MBC) in premenopausal women and summarizes the treatment options available in routine clinical practice. Knowledge of an up-to-date therapeutic approach in women with premenopausal HR+ MBC will lead to better disease management, thereby improving disease control and quality of life while minimizing side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 83 publications
0
18
0
1
Order By: Relevance
“…Patients with ER-positive tumors are treated with antiendocrine therapy inhibiting estrogen action by either aromatase inhibitors (AI) or selective estrogen receptor modulators (SERM) such as tamoxifen [5]. The latter is mainly used in premenopausal cases as aromatase inhibitors are more effective in menopausal women [6]. A major drawback of tamoxifen is therapy failure indicated by disease recurrence in about 20-30 per cent of tamoxifen-treated patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ER-positive tumors are treated with antiendocrine therapy inhibiting estrogen action by either aromatase inhibitors (AI) or selective estrogen receptor modulators (SERM) such as tamoxifen [5]. The latter is mainly used in premenopausal cases as aromatase inhibitors are more effective in menopausal women [6]. A major drawback of tamoxifen is therapy failure indicated by disease recurrence in about 20-30 per cent of tamoxifen-treated patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen (TAM) is the first line of therapy for the treatment of estrogen-receptor-positive breast cancer. This type of breast cancer develops TAM resistance, promoting tumor relapse (208). Phuong et al found that the MCF-7 breast cancer cell line showed TAM resistance (TAMR/MCF-7).…”
Section: Regulation Of the Pi3k/pten/akt/mtor Signaling Pathway By Dnmentioning
confidence: 99%
“…As for other combinations used in post-menopausal women, the application of such combinations in pre-menopausal setting needs proof of benefit and multiple trials are ongoing (161). For instance, regarding the use of mTORinhibitors + non-steroidal aromatase inhibitors in addition to GnRH agonist in premenopausal patients, data is still scarce.…”
Section: Pre-menopausal Vs Post-menopausalmentioning
confidence: 99%